Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to find the sum of the roots of the equation $$4(4^x + 4^{-x}) - 23(2^x + 2^{-x}) + 40 = 0 $$ in real numbers. I tried the substitution $ 2^x = t $ but then it turns into a quartic equation which I couldn't solve. I think its roots sum to zero so I want to prove it without actually finding the roots.

share|cite|improve this question
$$(2^x+2^{-x})^2=4^x+2+4^{-x}$$ may help here. – Oleg567 Jun 24 '14 at 10:43
up vote 3 down vote accepted

If $x$ is a root of this equation, then $-x$ is too. Thus, the sum of the roots is $0$.

share|cite|improve this answer
Your argument assumes that there is at least one solution. – gammatester Jun 24 '14 at 10:47
@gammatester: Nope. If there are no roots, the sum of no roots is still $0$. (While we're at it, if $0$ is a root, $-0$ isn't a separate root, but the contribution to the sum is still $0$.) – user2357112 Jun 24 '14 at 10:48

Let $2^x+2^{-x}=t$. Then $4(t^2-2)-23t+40=0 \implies 4t^2-23t+32=0$

share|cite|improve this answer


$$\implies 4\left[\left(a+\frac1a\right)^2-2\right]-23\left(a+\frac1a\right)+40=0$$

$\displaystyle a+\frac1a=b\implies 4(b^2-2)-23b+40=0\iff 4b^2-23b+32=0$

share|cite|improve this answer

First of all, if $\exists{r}\in\mathbb{R}$ such that $x=r$ is a solution, then $x=-r$ is also a solution.

So the sum of the roots of the equation (if there are any) is obviously $0$.

Second, here is a full analysis of your equation (from this link):

enter image description here

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.